Graphene oxide sheathed ZIF-8 microcrystals: engineered precursors of nitrogen-doped porous carbon for efficient oxygen reduction reaction (ORR) electrocatalysis - Thomas, Minju; Illathvalappi, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, Abdul Azeez Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ACS Applied Materials & Interfaces, 2016)
Nitrogen containing mesoporous carbon obtained by the pyrolysis of graphene oxide (GO) wrapped ZIF-8 (Zeolitic Imidazolate Frameworks-8) micro crystals is demonstrated to be an efficient catalyst for the oxygen reduction reaction (ORR). ZIF-8 synthesis in the presence of GO sheets helped to realize layers of graphene oxide over ZIF-8 microcrystals and the sphere-like structures thus obtained, on heat treatment, transformed to highly porous carbon with a nitrogen content of about 6.12% and surface area of 502 m(2)/g. These catalysts with a typical micromeso porous architecture exhibited an onset potential of 0.88Vvs RHE in a four electron pathway and also demonstrated superior durability in alkaline medium compared to that of the commercial Pt/C catalyst. The N-doped porous carbon derived from GO sheathed ZIF-8 core shell structures could therefore be employed as an efficient electrocatalyst for fuel cell applications.
Keywords: alkaline fuel cell; graphene oxide; N-doped carbon; oxygen reduction reaction; porous carbon; ZIF-8

Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction

Morphological ensembles of N-doped porous carbon derived from ZIF-8/Fe-graphene nanocomposites: processing and electrocatalytic studies - Thomas, Minju; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ChemistrySelect, 2018)
Engineering the active site density of porous carbon catalysts for enhanced electrocatalytic activity is the current focus in the quest for economically viable fuel cells. Herein, we synthesise ZIF-8/Fe-graphene composites for the formation of N and Fe co-doped carbon with diverse morphologies ranging from tubes and sheets to frameworks of carbon. A synthetic strategy involving the one pot synthesis of ZIF-8 based composites is accomplished by the reaction of 2-methylimidazole with mixed Zn/Fe salt solution containing graphene dispersions. The high temperature heat treatment of this precursor mix yielded micro-meso porous architectures of N, Fe co-doped carbon with dispersions of Fe/Fe3C. An onset potential value of 0.95 V and a half-wave potential of 0.82 V coupled with excellent durability and stability in alkaline medium indicated improved electrocatalytic performances over its commercial Pt/C counterpart. The appreciable electrocatalytic properties of the synthesized carbon are attributed to its morphological diversity, hybrid structure, high N doping and its heteroporous characteristics. The dispersed Fe/Fe3C and FeNx sites facilitated enhanced oxygen adsorption and the graphene inclusions in the composite provided retention of high nitrogen contents.
Keywords: electrocatalyst; fuel cell; N- Fe co-doped carbon; oxygen reduction reaction; ZIF-8

Fe3+ stabilized 3D cross-linked glycine-melamine formaldehyde networks as precursor for highly efficient oxygen reduction catalyst in alkaline media - Kottarathil, Shijina; Illathvalappil, Rajith; Nisa, S.; Sailaja, G. S.; Mohamed, Peer A.; Nair, Balagopal N.; Gopinathan, Anilkumar M.; Kurungot, Sreekumar; Yamaguchi, Takeo; Hareesh, U. S. (Materials Letters, 2020)
Development of inexpensive oxygen reduction electrocatalyst with high activity and durability is very important. Herein, iron carbide encapsulated pod-like graphitic carbon structures were prepared by simple pyrolysis involving Fe-glycine complex integrated melamine-formaldehyde resin precursor. The best catalyst among those studied, Fe-Gly 2 MF-C, possessing high degree of graphitization (I-D /I-G = 0.99) and enhanced specific surface area (205 m(2)/g) exhibited the highest ORR activity with a half-wave potential of 0.80 V in alkaline medium through the four-electron reduction pathway. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: fuel cell; Graphitic carbon alloy; Iron carbide; ORR

Template assisted synthesis of Ni,N co-doped porous carbon from Ni incorporated ZIF-8 frameworks for electrocatalytic oxygen reduction reaction - Priya K., Vaishna; Thomas, Minju; Illathvalappil, Rajith; K., Shijina; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2020)
A heteroatom doped porous carbon electrocatalyst with enhanced oxygen reduction reaction (ORR) performance in alkaline medium was obtained by high temperature treatment of Ni incorporated ZIF-8 frameworks and its composite with g-C(3)N(4)as a supporting matrix template. The morphology and porosity of this heteroatom containing carbon were tuned by varying the Ni : Zn molar ratio in Ni/Zn ZIF-8 and Ni/Zn ZIF-8@g-C(3)N(4)composites. The template aided synthetic strategy using g-C(3)N(4)helped in the controlled decomposition of composites leading to a heteroporous sheet like architecture with increased nitrogen content. The Ni/Zn ZIF-8 sample on heat treatment in the 800-1000 degrees C temperature range led to the formation of Ni,N co-doped porous carbon (Ni-NPC) with Ni-C active sites. The defective sites induced by nickel carbide along with the distributed N atoms on the carbon surface enabled active O(2)adsorption sites. The high surface area, high degree of graphitisation as well as the defects created by well dispersed N and Ni on porous carbon matrices favoured charge separation leading to higher electrochemical ORR activity. The Ni,N co-doped carbon catalyst in alkaline medium exhibited a limiting current density of 5.2 mA cm(-2)with a half-wave potential of 0.76 Vvs.RHE in 0.1 M KOH. The catalyst also showed improved methanol tolerance and better stability compared to the standard Pt/C catalyst.